Developing a procedure mimicking transvaginal mesh implantation in women in a modified POP rat model - Wang, Lulu; Long, Fang; Yan, Keqing; Li, Lutong; Gao, Na; Deqiong; Xiao, Zhen (Frontiers in Medicine, 2025)
IntroductionThis study aims to establish a simple and reproducible transvaginal mesh surgery rat model based on the modified pelvic organ prolapse rat model.MethodsA total of 24 10-week-old female nulliparous Wistar rats were used in this study. The control group consisted of six rats with no interventions. The ovariectomy group included six rats that underwent bilateral ovariectomy. The pelvic organ prolapse group comprised 12 rats that underwent cervical pendant modeling 2 weeks after bilateral ovariectomy. Fourteen days post-modeling, six rats from the pelvic organ prolapse group underwent transvaginal mesh surgery. The rat pelvic organ prolapse quantification system was used to evaluate the prolapse condition of the rats before and after pelvic organ prolapse modeling, as well as after transvaginal mesh surgery. Vaginal wall tissue was collected to assess biomechanical changes before and after pelvic organ prolapse modeling. Additionally, vaginal wall and sacral ligament tissues were collected to evaluate structural changes and collagen alterations before and after pelvic organ prolapse modeling.ResultsThe pelvic organ prolapse rat model exhibits anatomical prolapse, biomechanical changes, and pathological changes, including collagen fiber rupture and reduced collagen density. In contrast, the transvaginal mesh rat model demonstrates anatomical recovery in prolapsed rats.ConclusionThis study successfully modified the pre-existing rat model of pelvic organ prolapse and effectively mimicked human transvaginal mesh surgery using this model.